A COGNITIVE PRAGMATIC PERSPECTIVE ON EPISTEMIC MODALITY IN LITERARY DISCOURSE AND ITS PEDAGOGICAL IMPLICATIONS - Lalu Muhaimi; Sribagus .; Muhammad Fadjri (IAIN MADURA, 2017)
This is a cognitive pragmatic study of the use of the items of epistemic modality in a narrative fiction. The aims of this study are to identify, analyze and describe the ways the items of epistemic modality are used. Their contextual meanings, functions, and implication to the pedagogical attempts are also unfolded. The results of the interpretative and descriptive analysis reveal that the items of epistemic modality are found to be very dominant which also suggests that the genre of narrative fiction is linguistically characterized by the utterances that are established on the basis of knowledge and reasoning. The items of epistemic modality are found to be polysemous and poly-functional which are reflected pragmatically in the forms of politeness, negotiative and constructive functions. All these lead to the acknowledgement that the use of the items of linguistic modality in literary discourse and their usage for language teaching in the applied linguistic contexts is worth conducting.